Socioecological Risk and Protective Factors for Sexual Victimization in Post-Secondary Students in Ireland: A Brief Report - Mahon, Ciara (Journal of interpersonal violence, 2024)
Although numerous predictors of sexual violence (SV) have been identified, there is a need to further explore protective factors and examine the nature and strength of associations between predictors and SV outcomes using a hierarchical predictive model. Cross-sectional data from the My World Survey Post-Second Level (2019) in Ireland were used. The sample contained 8, 288 post-secondary students, 69% female, aged 18 to 25 years (M = 20.25, SD = 1.85). Univariate and multivariate binary logistic regression analyses were conducted to identify correlates of two SV outcomes (i.e., forced/pressured to have sex and being touched in a sexual manner without consent) across societal, community, relationship, and individual levels. Approximately 25% of females and 10% of males reported being forced/pressured to have sex, whereas 55% of females and 23% of males reported being touched in a sexual manner without consent. Key predictors of SV in multivariate analyses included being female and experiencing violence in a romantic relationship, whereas discrimination, living on campus or in rented accommodation (compared with living at home) were also significant predictors of both SV outcomes. Parental conflict, sexual initiation, depressive symptoms, older age, and an avoidant coping style significantly predicted being forced/pressured to have sex, whereas being bullied and engaging in problem drinking were unique predictors of being touched sexually without consent. Findings highlight the importance of considering salient risk and protective factors at the individual, relationship, community and societal level to predict SV and effectively guide the delivery of interventions and support services for post-secondary students affected by SV.